Synchronized time-lens source for coherent Raman scattering microscopy - Wang, Ke (Optical Society of America, 2010)
We use the time-lens concept to demonstrate a new scheme for synchronization of two pulsed light sources for biological imaging. An all fiber, 1064 nm time-lens source is synchronized to a picosecond solid-state Ti: Sapphire mode-locked laser by using the mode-locked laser pulses as the clock. We demonstrate the application of this synchronized source for CARS and SRS imaging by imaging mouse tissues. Synchronized two wavelength pulsed source is an important technical difficulty for CARS and SRS imaging. The time-lens source demonstrated here may provide an all fiber, user friendly alternative for future SRS imaging.